From performers to spectactivists: Jana Sanskriti's training for agency in and beyond theatre. Issue 1 (1st April 2017) - Yarrow, Ralph
Sanjoy Ganguly and his company, Jana Sanskiti (Badu, West Bengal), operate a mode of training that works with individuals, groups and communities to develop cognitive, motoric and affective agency. This enables them to become fully involved participants in the collective refashioning of their political and social situation. Their work involves the acknowledgement and activation of bodies and their performative, relational and agential capacities. It draws on Boal's use of theatre games and exercises and extends this by the addition of aspects of Indian folk practice, and the precise operation of a sequential strategy across time that embodies successive phases of recognition and analysis by means of different modalities of interactive work: the acquisition of skills and techniques, ways of drawing on performance knowledges, institution of co-creativity and collaborative scripting, and the extension of these capacities to community activism. This article will trace these dimensions of Jana Sanskriti's work and relate them to understandings of forms of embodied knowing.